Empirical Testing of Fama-French Asset Pricing Five Factor Model In Indonesia Stock Exchange During The Covid-19 Pandemic Period - Sitanggang, Okta Martua; Rizkianto, Eko (AFEBI Economic and Finance Review, 2023)
The volatility of the Indonesian Stock Exchange Composite (JKSE) increased significantly during the Covid-19 pandemic period. In this period, return predictability and price volatility in the stock index experienced a single structural break. There is concern among investors and academics that the asset pricing model that has been empirically accepted so far is unable to explain the return or excess return of an asset or investment during the Covid-19 pandemic period. This research empirically tests the significance of Fama – French Five Factor Model. The significance of factors consists of size (market capitalization), profitability, value (book-to-market), investment, and market risk premium (Rm-Rf) factors explain the excess return of stock portfolios on the Indonesian Stock Exchange during the Covid-19 pandemic period. Existing studies show that the Covid-19 pandemic has affected investor sentiment, causing investors to panic and be pessimistic about their investments. In addition, there were deviations from the efficient market hypothesis during several pandemic periods in several countries so that stock prices did not fully reflect the available information. After testing, it was found that the factors size (market capitalization), profitability, value (book-to-market), investment, and market risk premium (Rm-Rf) did not have a significant influence on the excess return of stock portfolios on the Indonesia Stock Exchange during the period Covid-19 pandemic. Keywords: asset pricing; structural break; Fama-French